Hyobanche thinophila (Orobanchaceae), a new species from the Western Cape of South Africa - Wolfe, Andrea D. (Phytotaxa, 2013)
The new species Hyobanche thinophila is described and illustrated. It is distinguished from H. sanguinea by the absence of glandular hairs on the interior surface of the corolla, and differences in the shape and color of the corolla and inflorescence. The interior surface of the H. thinophila corolla is glabrous except for a zone of long multicellular hairs at the level of stamen insertion. Hyobanche sanguinea lacks this character. The new species occurs in dune areas along the coast of Western Cape, South Africa.